1968
DOI: 10.1017/s0031182000069705
|View full text |Cite
|
Sign up to set email alerts
|

Passive protection with cells or antiserum against Nippostrongylus brasiliensis in the rat

Abstract: Rats can be passively protected against N. brasiliensis either with antiserum or with cells. Only some pools of antiserum (15 of 48 pools) and a few batches of cells (three of 11 batches) were protective.Protective activity was found in serum taken after one infection as frequently as after several infections and gave the same degree of protection. This suggests that second and subsequent infections do not stimulate an anamnestic increase in protective antibodies in the circulation.Serum and cells taken from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…There was also a suggestion that a cellular compartment may be involved in protection, although exactly what cells were important and how they contributed were unclear (16). This idea was extended several decades later through a series of papers from Ogilvie and colleagues (22)(23)(24), again working with N. brasiliensis in the rat, together with studies from Dineen and colleagues (25)(26)(27) using the ovine parasite Trichostrongylus colobriformis, in this case a sheep parasite adapted to the guinea pig. Ogilvie and coworkers developed the idea in the 1960s and 1970s of protective immunity operating through antibody and cells-lymphocytes-and also identified [alongside other groups, e.g., Jarrett (28,29)] the highly elevated IgE levels that were associated with worm infection.…”
Section: Setting the Scenementioning
confidence: 99%
See 1 more Smart Citation
“…There was also a suggestion that a cellular compartment may be involved in protection, although exactly what cells were important and how they contributed were unclear (16). This idea was extended several decades later through a series of papers from Ogilvie and colleagues (22)(23)(24), again working with N. brasiliensis in the rat, together with studies from Dineen and colleagues (25)(26)(27) using the ovine parasite Trichostrongylus colobriformis, in this case a sheep parasite adapted to the guinea pig. Ogilvie and coworkers developed the idea in the 1960s and 1970s of protective immunity operating through antibody and cells-lymphocytes-and also identified [alongside other groups, e.g., Jarrett (28,29)] the highly elevated IgE levels that were associated with worm infection.…”
Section: Setting the Scenementioning
confidence: 99%
“…The early work based on passive transfer of sera taken from immune or hyperimmune (e.g., repeatedly challenged) animals suggested that antibody did reduce both intestinal worm burdens (and/or egg output from female worms), with precipitates forming around and within parasites. These findings suggested that blocking or neutralizing key functions of the parasite contributed to worm damage (23,24,(43)(44)(45). Few studies examined the class of antibody that mediated protection, although work from the H. polygyrus bakeri system (formally Nematospiroides dubius) identified IgG1 as the class of antibody involved (46,47).…”
Section: Setting the Scenementioning
confidence: 99%
“…Thus, these observations are not necessarily opposed to the hypothesis that anaphylactic antibodies might play a role in the elimination of the parasites. As mentioned earlier, recent observations by O gilvie et al [29] are not in favour of such a concept.…”
Section: Discussionmentioning
confidence: 79%
“…The mechanism of self-cure is still poorly understood. Various reports have shown that it is possible passively to protect rats against Nippostrongylus brasiliensis infections with antiserum [6,25,29,36]. Recent findings [29] have indicated, however, that there is no correlation between the appearance of protective and anaphylactic antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, protective antibodies are not present in all sera from infected rats, and they are no more readily demonstrable in rats infected more than once than in those receiving a single infection [8]. The same situation may also occur with cellular im munity since lymph node cells from singly infected rats are probably as efficient, if not more so, than cells from repeatedly infected rats in the transfer of passive immunity [7], Earlier attempts to transfer immunity with cells provided extremely erratic results (reviewed by O gilvie and J ones [9]).…”
Section: Discussionmentioning
confidence: 99%